Screening For Antimicrobial Properties Of Vitex Negundo. L From Rural Areas Of Warangal Dist. A.P. India - SRINIVAS P; RAM REDDY S; PALLAVI P; SURESH A; PRAVEEN V (International Journal of Pharma and Bio Sciences, 2010)
Antimicrobial properties of different parts of Vitex negundo were evaluated on bacterial strains viz, Bacillus cereus ATCC 11778, Bacillus subtilis ATCC 6633, Staphylococcus epidermidis ATCC 12228, Enterobacter aerogenes ATCC 13046, Escherichia coli ATCC 25922, Klebsiella Pneumoniae NCIM 2719, Proteus vulgaris NCTC 8313, Pseudomonas aeruginosa ATCC 27853,Psuedomonas putida ATCC 12842, Salmonella typhimurium ATCC 23564. The solvents used for extraction of plant parts were hexane, chloroform and methanol. In vitro antibacterial activity was tested by agar diffusion method. The most susceptible gram positive bacteria was Bacillus cereus, while the most susceptible gram negative bacteria were Klebsiella pneumonia, Pseudomonas aeruginosa, Pseudomonas putida. The extracts of root and bark have shown moderate antimicrobial activity when compared with flower and leaves. Among these bacteria Proteus vulgaris is resistant against all extracts of leaves and flowers. Intermediate activity was observed with bark and root extracts. The significance of antibacterial activity of active extracts was compared with standard antimicrobics; streptomycin 2mg/cup.The results obtained in the present study suggest that Vitex negundo can be used in treating diseases caused by test organisms.